Respuesta :
The answer to the question should be n = 2.
This is because we can start by setting up the equation as this:
3/5n - 4/5 = 1/5n.
Next we would subtract 3/5n from both sides.
-4/5 = -2/5n.
Then we would multiply both sides by 5/-2.
2 = n.
This is because we can start by setting up the equation as this:
3/5n - 4/5 = 1/5n.
Next we would subtract 3/5n from both sides.
-4/5 = -2/5n.
Then we would multiply both sides by 5/-2.
2 = n.
Answer:
n = 2
Step-by-step explanation:
As per statement of the question we will form the equation first.
[tex](\frac{3}{5})n-\frac{4}{5}=(\frac{1}{5})n[/tex]
Now we will solve the given equation to get the solution of n.
[tex](\frac{3}{5})n=\frac{4}{5}+(\frac{1}{5})n[/tex]
[tex](\frac{3}{5})n-(\frac{1}{5})n=\frac{4}{5}[/tex]
[tex](\frac{3-1}{5})n=\frac{4}{5}[/tex]
[tex](\frac{2}{5})n= \frac{4}{5}[/tex]
Now we cross multiply the fractions
(2×5)×n = 4×5
10.n = 20
[tex]n=\frac{10}{5}=2[/tex]
Therefore answer is n = 2